Build Character Responsibilities of Junior High School Students Based on the Values of the Qur'an and Hadith: A Literature Review - Galby Silvia Rachmah; Imroh Atul Musfiroh; Moh Mahrus; Iskandar Iskandar; Mahyuddin Barni (Borneo International Journal of Islamic Studies, 2025)
This study examines how the Qur'an and Hadith provide a conceptual and pedagogical foundation for character education in Islamic education. While character education has gained increasing attention in contemporary educational discourse, limited studies have systematically connected classical Islamic sources with modern pedagogical frameworks. Employing a qualitative library research design, this study uses textual analysis and thematic interpretation of selected Qur'anic verses (QS Al-Baqarah 267–268; QS Al-'Alaq 1–5) and authentic hadith narrated by Bukhari and Muslim to identify key principles of character formation and instructional practice. The findings indicate that QS Al-Baqarah 267–268 promotes generosity, integrity, empathy, and psychological resilience, whereas QS Al-'Alaq 1–5 underscores the importance of knowledge acquisition, intellectual humility, and ethical learning. The analysis of prophetic traditions further reveals pedagogical principles, including gradual instruction (tadarruj), facilitation rather than complication (taysir), positive reinforcement, and systematic repetition to support learning mastery. These principles show strong conceptual alignment with contemporary educational perspectives, including differentiated instruction, mastery learning, growth mindset, and positive psychology. The study also highlights the collaborative roles of families, schools, and communities in fostering holistic character development. By integrating Islamic educational values with contemporary pedagogical theories, this study contributes to the literature on values-based education and demonstrates the continued relevance of Qur'anic and Prophetic teachings for developing learners who are intellectually capable, morally responsible, socially engaged, and spiritually grounded in addressing the challenges of the twenty-first century.